MPI impact in C+L+S multiband transmission reach - Cancela, L.; Pires, J. (Proceedings Advanced Photonics Congress 2024, 2024)
Multipath interference (MPI) impact is assessed in a C+L+S multiband transmission scenario. For a typical -34 dB/span MPI, transmission reach in the L-band suffers a 20% reach penalty considering the QPSK modulation format.